Hermeneutic courage. What Gadamer (and Arendt) can tell us about political thinking - Sam McChesney (Labyrinth: An International Journal for Philosophy, Value Theory and Sociocultural Hermeneutics, 2022)
Hans-Georg Gadamer, despite his exchanges with and reception by major figures in the field of political theory, is often thought of as a philosopher as opposed to a political theorist. For instance, the title of one of his essays, "On the Political Incompetence of Philosophy," is sometimes taken to indicate that Gadamer thought of his own philosophy as "politically incompetent" (Code 2003, 15). In this paper, I argue that Gadamer's hermeneutic philosophy is deeply concerned with our relation to the political world. To bring out these political concerns, I put Gadamer in conversation with Hannah Arendt, who overtly disavowed philosophy in favor of political theory. I show that Gadamer and Arendt share many of the same worries about the solitary model of much philosophy – particularly that of Heidegger – and that both try to promote a more involved, worldly mode of thinking. For Arendt, this mode of thinking attends in large part to the newness and distinctiveness of other people, whereas Gadamer emphasizes what other people say and how we must relate to them if we are to understand what they are telling us. I argue that although these are complementary ways of addressing political thinking, one important advantage of Gadamer's account is the way it brings into view the centrality of courage for understanding our shared political world. Because understanding frequently requires that we question our identities and renegotiate our existing relation to the world in often uncomfortable ways, political thinking involves what I call "hermeneutic courage.".